Is initial interfragmentary compression made to last? An ovine bone in vitro study. Issue 6 (June 2021) - Keltz, Eran; Mora, Alberto Jorge; Wulsten, Dag; Rußow, Gabriele; Märdian, Sven; Duda, Georg N.; Heyland, Mark
Highlights: Interfragmentary compression is clinically not quantified and might be lost. Compression plate or lag screw fixation reliably achieve compression in ovine bone. Applied compression varies more within fixation groups than between groups. Interfragmentary stress relaxation minimal over first hour. Functional loads might overcome compression force. Abstract: Interfragmentary compression, a major principle of fracture treatment, is clinically not quantified and might be lost quickly even without functional loads. We designed an experimental study hypothesizing that (1) compression can be controlled using either lag screw or compression plate, and expecting similar initial compression, (2) loss of interfragmentary compression through relaxation within one hour is reduced with neutralization locking plate next to lag screw compared to compression plate. Twelve ovine femora ( N =6) and humeri ( N =6) were assigned into groups: Group 1 received a 45° oblique osteotomy at mid-diaphysis and was fixated using a 3.5 mm interfragmentary lag screw and locking compression plate (3.5 mm LCP, DePuy Synthes) as neutralization plate. Group 2 received a transverse osteotomy and was fixated with dynamic compression using compression plate (LCP). Interfragmentary pressure and relative bone fragment displacements were recorded over one hour. Median loss of compression over one hour time (relaxation) were 0.52% in Group 1, and 0.17% in Group 2 ( p >0.05). Median rotational displacements amounted to 0.46° for Group 1, and 0.31° for Group 2, and axial displacement to a median of −20 μm in Group 1 and 25 μm in Group 2. Ovine bone interfragmentary stress relaxation maintains compression over the first hour for lag screw with neutralization plate for an oblique fracture line or compression plate for a transverse fracture line. Measured compression forces around 100 N could be overcome by physiological tension loading in bending or torsion, necessitating for instance tension band plating, additional lag screws or absolutive stability.